2008
DOI: 10.1007/s00216-008-2046-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of interactions between polyphenolic compounds and human serum proteins by capillary electrophoresis

Abstract: The interaction of ten natural polyphenolic compounds (chlorogenic acid, apigenin, catechin, epicatechin, flavanone, flavone, quercetin, rutin, vicenin-2 and vitexin) with human serum albumin and mixtures of human serum albumin and α(1)-acid glycoprotein under near physiological conditions is studied by capillary electrophoresis-frontal analysis. Furthermore, the binding of these polyphenolic compounds to total plasmatic proteins is evaluated using ultrafiltration and capillary electrophoresis. In spite of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 17 publications
4
40
0
1
Order By: Relevance
“…We immediately thought that heme-containing proteins were potentially important quercetin-binding molecules since our previous work performed in RBC provided evidence of remarkable accumulation dependent on extensive binding of the flavonoid to hemoglobin [12,[40][41][42]. Quercetin binding to hemoglobin was recently documented by fluorescence quenching as well as by absorption and circular dichroism spectroscopy [43].…”
Section: Discussionmentioning
confidence: 99%
“…We immediately thought that heme-containing proteins were potentially important quercetin-binding molecules since our previous work performed in RBC provided evidence of remarkable accumulation dependent on extensive binding of the flavonoid to hemoglobin [12,[40][41][42]. Quercetin binding to hemoglobin was recently documented by fluorescence quenching as well as by absorption and circular dichroism spectroscopy [43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that catechins form complexes with human serum albumin (HSA), and differences in binding affinity toward HSA are believed to determine their bioavailability. Several reports using spectrofluorometry, circular dichroism, and capillary electrophoresis have indicated that green tea catechins bind to HSA (12)(13)(14). Recently, we revealed that EGCg non-covalently binds to HSA after incubation of human serum with EGCg ( 15 ).…”
mentioning
confidence: 85%
“…ACE in the frontal analysis format has primarily been used to investigate plasma protein binding of small molecules [33][34][35][36][37], and to a certain extent ligand-electrolyte interactions [37,38]. Kuroda et al used liposomes as a model of lowdensity lipoproteins to study the interactions between the drug compounds propranolol and verapamil and liposomes in the CE frontal analysis (CE-FA) format [39].…”
Section: Liposomes Have Been Introduced As Pseudostationary Phasesmentioning
confidence: 99%